Membangun Kerukunan Hidup Berbangsa Dalam Konteks Pluralisme Agama–agama di Indonesia - Rosmawati Ndraha (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2022)
The Indonesian people live in various differences, ethnicity, culture, language, religion. This difference is a priceless wealth of the nation. However, if it is not managed properly, it will turn into an enormous threat to the unity and integrity of the nation. Religious harmony is a relationship among religious communities based on tolerance, mutual understanding, mutual respect, respect for equality in the practice of their religion and cooperation in social, national and state life within the Unitary State of the Republic of Indonesia. To realize this harmony, the state makes laws and regulations regarding the maintenance of religious harmony. UUD 29 of the 1945 Constitution states that the state is based on Belief in One Almighty God and guarantees the freedom of the population to embrace religion and practice worship according to their beliefs. The government as the leader of the country has provided a number of laws and regulations which, if obeyed by the public, will become a means of unifying a nation that is rich in diversity. The government cannot work alone to create and maintain this harmony, bearing in mind that this involves a lot of issues of beliefs and principles that the community adheres to. The government must partner with: Religious leaders, whose role is to provide understanding to their respective followers in fostering and preserving inter-religious harmony in accordance with their religious teachings. Community leaders as people who are imitated by certain community groups act as facilitators to bridge communication and interests within diverse community groups. Maintenance of religious harmony is a joint effort made between religious communities and the government in the field of service, regulation, and empowerment of religious communities through inter-religious dialogue